Social Media and Poverty: Paradoxes of Communicating Poverty Issues on Social Media - Wahyunengseh, Rutiana Dwi; Hastjarjo, Sri; Suharto, Didik G. (UI Scholars Hub, 2018)
From the democratic theory perspective, social media is a means to improve collaborative public governance between government, society, and business sector, in order to ensure effective public issues management as well as public services. On the other hand, there are preconditions for the effective use of media social; in the context of addressing poverty issues, these preconditions have potential to generate certain paradoxes. This article aims to answer a question “Is the use of social media effective to the poverty alleviation mainstreaming issue?” This study was conducted in one of the cities that won Smart City Award in Indonesia; using content analysis on the